2022
DOI: 10.1016/j.apsb.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical applications of framework nucleic acids

Abstract: DNA is a biological polymer that encodes and stores genetic information in all living organism. Particularly, the precise nucleobase pairing inside DNA is exploited for the self-assembling of nanostructures with defined size, shape and functionality. These DNA nanostructures are known as framework nucleic acids (FNAs) for their skeleton-like features. Recently, FNAs have been explored in various fields ranging from physics, chemistry to biology. In this review, we mainly focus on the recent progress of FNAs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 149 publications
(155 reference statements)
0
24
0
Order By: Relevance
“…Indeed, the choice of nucleotide(s) will improve the solubility of the nucleopeptides because of the presence of negatively charged phosphate groups, whereas the incorporation of nucleobases directly grafted, nucleosides and especially PNA, which are exempt of charge, will have the opposite effect with a higher propensity to aggregation and/or precipitation. 29,43,44 All these derivatives have a good biocompatibility, 40,107–109 as confirmed by several examples ( e.g. , (15) , 77 (25) , 67 (30) , 97–99 (41) 102 ), though with better chemical ( i.e.…”
Section: Summary Conclusion and Perspectives Of Low-molecular Weight ...mentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, the choice of nucleotide(s) will improve the solubility of the nucleopeptides because of the presence of negatively charged phosphate groups, whereas the incorporation of nucleobases directly grafted, nucleosides and especially PNA, which are exempt of charge, will have the opposite effect with a higher propensity to aggregation and/or precipitation. 29,43,44 All these derivatives have a good biocompatibility, 40,107–109 as confirmed by several examples ( e.g. , (15) , 77 (25) , 67 (30) , 97–99 (41) 102 ), though with better chemical ( i.e.…”
Section: Summary Conclusion and Perspectives Of Low-molecular Weight ...mentioning
confidence: 80%
“…Indeed, the choice of nucleotide(s) will improve the solubility of the nucleopeptides because of the presence of negatively charged phosphate groups, whereas the incorporation of nucleobases directly grafted, nucleosides and especially PNA, which are exempt of charge, will have the opposite effect with a higher propensity to aggregation and/or precipitation. 29,43,44 All these derivatives have a good biocompatibility, 40,[107][108][109] as confirmed by several examples (e.g., (15), 77 (25), 67 (30), [97][98][99] (41) 102 ), though with better chemical (i.e., against hydrolysis and depurination) and biological (i.e., against nucleases) stability for nucleobase(s) directly grafted and PNA. 43,44,80,81 Also, nucleotides and PNA offer the possibility for incorporating several nucleobases in a row (i.e., strands), even if such an approach presents challenges in terms of chemical synthesis.…”
Section: Summary Conclusion and Perspectives Of Low-molecular Weight ...mentioning
confidence: 99%
“…FNAs are 1D to 3D nanostructures formed from DNA/RNA molecules that assemble based on the Watson-Crick base complementary pairing principle. 204 , 205 , 206 A tetrahedral framework nucleic acid (tFNA) is a simple 3D structure with abundant functional modification sites that is formed by four different single strands of DNA (ssDNA) through DNA origami technology. 207 , 208 Several studies have shown that tFNA has the function of promoting angiogenesis through activation of signaling pathways, such as Notch signaling, 209 JAK/STAT signaling, 210 and the Akt/Nrf2/HO-1 pathway.…”
Section: Gene-silencing-based Therapeutics For Wound Angiogenesismentioning
confidence: 99%
“…14 DNA as a building material has great potential to create a drug delivery vehicle responding to endogenous triggers. [15][16][17][18] The triggered hybridization of DNA can produce forces large enough to facilitate the transition between secondary structures. [19][20][21] It has been previously shown that the binding of an aptamer sequence to its target structure can displace pre-hybridized complementary DNA from the aptamer.…”
Section: Textmentioning
confidence: 99%